FACTORS INFLUENCING EXPECTANT MOTHERS' CONTINUED USE OF DIGITAL HEALTH INFORMATION - Philomina Pomaah Ofori; Kumangkem Kennedy Kubuga; Dominic Kofi Louis (Universitas Airlangga, 2023)
Background: Expectant women receive healthcare education at antenatal care (ANC) clinics, but it is noteworthy that expectant mothers tend to seek information from various sources beyond their primary healthcare providers. Aims: The study aims to investigate determinants influencing expectant mothers' continuous use of digital media for pregnancy information. Methods: The study involves participants of expectant women who attend ANC clinics in five municipal hospitals. The hypotheses were tested with 580 responses using Structural Equation Modeling (SEM) via SmartPLS version 4. Results: The findings revealed that social media healthcare information usage, perceived severity, and emotional support on social media influence expectant mothers' decisions to continue using digital media for healthcare purposes. However, the effect of perceived vulnerability on social media healthcare information usage was insignificant. Conclusion: This study concludes that expectant mothers will continue to adopt digital platforms to access healthcare information. The findings provide recommendations to help healthcare providers advance antenatal care. Keywords: Emotional support, healthcare, expectant women, SMHIC, social media